The Effect Of Concentration and Duration Of Coconut Water Soaking On the Growth Of Oil Palm Seeds in Pre-Nursery (Elaeis Guineensis Jacq.) - Lince Romauli Panataria; Agnes Imelda Manurung; Efbertias Sitorus; Meylin Kristina Saragih (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to determine the effect of soaking time and coconut water concentration on the dormancy breaking of oil palm seeds (Elaeis guineensis Jacq.). This study used a Factorial Completely Randomized Design with two factors. The first factor is the concentration of coconut water (A): A1 = 25% coconut water/liter of water, A2 = 50% coconut water/liter of water, and A3 = 75% coconut water/liter of water. The second factor is the soaking time (L): L1 = 30 minutes, L2 = 60 minutes, and L3 = 90 minutes. Data analysis was conducted using variance analysis and Duncan's test. The results showed that the concentration of coconut water significantly affected germination power, germination age, plant height, and the number of leaves of oil palm seedlings. A 75% concentration of coconut water produced the best dormancy breaking of oil palm seeds. The soaking time in coconut water solution also significantly affected germination power, germination age, plant height, and the number of leaves of oil palm seedlings. A soaking time of 90 minutes resulted in the best dormancy breaking of oil palm seeds. The interaction between coconut water concentration and soaking time significantly affected the germination power of oil palm seeds. This study provides important information on the optimal soaking conditions to improve dormancy breaking success, which can be used to accelerate the germination and growth of oil palm seedlings.